Ganglion of the Sternoclavicular Joint: A Rare Location of an Uncommon Pediatric Mass - Jacob Musiol; Jacob Hansen; Jonathan Wood (Case Reports in Radiology)
This is a case of a two-year-old boy with a ganglion arising from the sternoclavicular joint. Ganglia are rare in the pediatric population, with less than 2% occurring under the age of 2 years old. Additionally, sternoclavicular joint ganglia are also exceedingly rare. The case illustrates the importance of keeping ganglion within the differential diagnosis for palpable subcutaneous masses, even in young children, especially when they are seen to connect to the joint.